2017
DOI: 10.1093/jamia/ocx149
|View full text |Cite
|
Sign up to set email alerts
|

Patient portal use and hospital outcomes

Abstract: Use of the patient portal in the inpatient setting may not improve hospital outcomes. Future research should examine the association of portal use with more immediate inpatient health outcomes such as patient experience, patient engagement, medication reconciliation, and prevention of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 24 publications
0
45
0
1
Order By: Relevance
“…Over half of our inpatient oncology population voluntarily adopted the portal before hospital admission and 27% actively used the portal during the stay. Dumitrascu et al found that of 44.2% patients who had a portal account at the time of admission, only 20.8% accessed the portal during their stay [ 48 ]. Davis et al found that of 34.4% registered portal patients, 23.4% used it while hospitalized [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over half of our inpatient oncology population voluntarily adopted the portal before hospital admission and 27% actively used the portal during the stay. Dumitrascu et al found that of 44.2% patients who had a portal account at the time of admission, only 20.8% accessed the portal during their stay [ 48 ]. Davis et al found that of 34.4% registered portal patients, 23.4% used it while hospitalized [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Continuity of Care Document, a complete summary of patient current health status and history, is also available to view, download, or forward to physicians at other hospitals. Additional information on MCF patient portal is documented elsewhere [ 48 ]. Although the portal is designed for outpatients, some functions are applicable to inpatient health information needs during the hospital stay.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted at Mayo Clinic in Florida reported no differences in 30day hospital readmissions between a group provided with an inpatient portal and a propensity score matched cohort (P ¼ 0.13). 54 Further research should explore the potential impact of inpatient portals on readmission, as well as the influence of potential effect modifiers such as relationship with healthcare providers or socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that younger participants were more likely to use the inpatient portal was consistent with previous research. 54 Another limitation was that we did not assess cognitive status that may have impacted the study beyond an initial screening using the Mini-Mental Status Examination. With respect to analyzing hospital readmissions, we did not have access to hospitalization records outside of our hospital system.…”
Section: Limitationsmentioning
confidence: 99%
“…Overall, access to information and secure messaging are probably one facet of patient satisfaction; it is, therefore, questionable whether the impact of a patient portal on patient satisfaction is measurable [19]. Thus, there is a need for further research that focuses on use of the patient portal and measures of patient satisfaction [18,20].…”
Section: Introductionmentioning
confidence: 99%